Atrial Fibrillation in the Arab World: A Bibliometric Analysis of Research Activity from 2004 to 2019 - Akiki, Dany; El Hage, Said; Wakim, Elias; Safi, Steven; Assouad, Elise; Salameh, Pascale (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Background: Atrial fibrillation (AF) is in an increasing pattern worldwide, especially in the Arab world. Objective: The aim of this article is to assess AF research activity in the Arab countries over the past 16 years, taking into consideration the population size, gross domestic product (GDP) and disability-adjusted life years (DALY). Methods: Atrial fibrillation related research articles published from Arab countries between 2004 and 2019 were collected from the MEDLINE database and are cited online on PubMed. Medical Subject Heading (MeSH) terms related to the subject, the origin and the date of publication were used to search for the published articles. Results: The number of AF related publications in the Arab world over the past 16 years was only 283 (0.73%) out of a total of 38,983 publications worldwide. Saudi Arabia ranked first in terms of number of AF related publications, followed by Egypt. Lebanon is the country with the highest number of publications per USD billion GDP, while Egypt and Saudi Arabia have the highest number of publications per 1% DALYs. According to the population size, Qatar and Bahrain produced the highest number of publications per million persons (PPMP). A strong and positive correlation was found between the number of publications and the GDP. The population size and the percentage of DALY showed positive yet weak correlation. Conclusion: A slight increase in AF related publications is observed. Nonetheless, AF research activity in the Arab world is still insufficient.